2009
DOI: 10.1007/s00455-008-9193-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity and Swallowing

Abstract: Recent research has suggested that the central nervous system controlling swallowing can undergo experience-dependent plasticity. Moreover, swallowing neuroplastic change may be associated with behavioural modulation. This article presents research evidence suggesting that nonbehavioural and behavioural interventions, as well as injury, can induce swallowing neuroplasticity. These studies indicate that while swallowing and limb neuroplasticity share certain features, certain principles of swallowing neuroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 97 publications
2
65
0
Order By: Relevance
“…A number of studies have suggested that heightening the sensory input via sensory techniques may be the best approach to managing CNS oropharyngeal dysphagia [8][9][10][11][12][13][14]. The provision of increased or specific sensory input to the oropharyngeal receptors might enhance the excitability of the central pathway.…”
mentioning
confidence: 99%
“…A number of studies have suggested that heightening the sensory input via sensory techniques may be the best approach to managing CNS oropharyngeal dysphagia [8][9][10][11][12][13][14]. The provision of increased or specific sensory input to the oropharyngeal receptors might enhance the excitability of the central pathway.…”
mentioning
confidence: 99%
“…15 More recently, there is growing evidence that the neural network for swallowing is capable of experience-dependent plasticity. 16 This in turn has fuelled the development of several experimental interventions for dysphagia. For example, sensory stimulation of the oropharynx with airpulse trains has been shown to increase resting swallowing rates in tube-fed patients with dysphagia after stroke 17 and activate the cortical swallowing network in controls.…”
mentioning
confidence: 99%
“…This evidence includes (i) the extensive connections between face SI and MI, (ii) motor outputs from SI as well as MI to brainstem regions involved in motor as well as somatosensory functions, and (iii) the SI and MI neuronal motor-related activity patterns and motor effects of SI or MI stimulation or lesions (see Refs. [2,[6][7][8][9][10]) as noted below.…”
Section: Overview Of Orofacial Sensorimotor Circuits and Role Of Facementioning
confidence: 97%